2022
DOI: 10.1016/j.dld.2022.01.128
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 and HER2 expression in gastric adenocarcinoma and their prognostic significance

Abstract: Background: The upregulation of programmed death-ligand 1 (PD-L1) and epidermal growth factor receptor 2 (HER2) may play a role in gastric adenocarcinoma (GAC). Aim: To study PD-L1 and HER-2 expression and prognosis in GAC. Methods: PD-L1 and HER2 expression was determined in tumor tissues of 75 patients with GAC. The correlations between PD-L1, HER2 expression, and clinicopathological factors were analyzed. Results: The positive expression rate for PD-L1 was 57.3% (43/75) and the HER2 over-expression rate was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…A significant prognostic value of ERBB2 CN, TMB and genomic alterations associated with HER2 signaling could not be confirmed in this cohort. PD-L1 expression has been found to co-occur with HER2-positivity in 25-85% of GC/GEJ patients [21][22][23]32]. With 47.3% of HER2+/PD-L1+ patients, our result falls within the reported range.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A significant prognostic value of ERBB2 CN, TMB and genomic alterations associated with HER2 signaling could not be confirmed in this cohort. PD-L1 expression has been found to co-occur with HER2-positivity in 25-85% of GC/GEJ patients [21][22][23]32]. With 47.3% of HER2+/PD-L1+ patients, our result falls within the reported range.…”
Section: Discussionsupporting
confidence: 77%
“…Recent studies like the KEYNOTE-811 explored the efficacy of anti-PD-L1 treatment in HER2-positive mGC/mGEJC showing that the combination of pembrolizumab and trastuzumab with chemotherapy leads to improved response rates compared to treatment with chemotherapy and trastuzumab alone [21]. In addition, the combined expression of PD-L1 and HER2 was found to be a positive prognostic factor for survival in GC [22]. Findings from a preliminary biomarker analysis of the DESTINY-Gastric03 trial, showed a large overlap between HER2 and PD-L1 expression in 85% of the patients GC or GEJC [23].…”
Section: Introductionmentioning
confidence: 99%
“…HER2 overexpression correlates with PD-L1 overexpression [ 138 ]. One study found that HER2 knockdown in PD-L1/HER2+ GC organoids resulted in a decrease in PD-L1 expression [ 139 ].…”
Section: Her2 Overexpression In Gastric Cancermentioning
confidence: 99%
“…Furthermore, in co-cultures with immune cells, cytotoxic lymphocytes proliferated more and caused an increase in tumour cell death [ 139 ]. Another study reported that 85% of HER2-positive gastric adenocarcinoma (GACs) were characterized by a positive PD-L1 expression and PD-L1 expression positively correlated with HER2 overexpression [ 138 ]. These data showed that the combination of anti-PD-L1 treatment with anti-HER2 therapy may have a positive effect in AGC patients with HER2 overexpression [ 138 ].…”
Section: Her2 Overexpression In Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation